Shielding of viruses such as SARS-Cov-2 from ultraviolet radiation in particles generated by sneezing or coughing: Numerical simulations of survival fractions. Issue 8 (3rd August 2021) - Hill, Steven C.; Mackowski, Daniel W.; Doughty, David C.
Abstract: SARS-CoV-2 and other microbes within aerosol particles can be partially shielded from UV radiation. The particles refract and absorb light, and thereby reduce the UV intensity at various locations within the particle. Previously, we demonstrated shielding in calculations of UV intensities within spherical approximations of SARS-CoV-2 virions within spherical particles approximating dried-to-equilibrium respiratory fluids. The purpose of this paper is to extend that work to survival fractions of virions (i.e., fractions of virions that can infect cells) within spherical particles approximating dried respiratory fluids, and to investigate the implications of these calculations for using UV light for disinfection. The particles may be on a surface or in air. Here, the survival fraction ( S ) of a set of individual virions illuminated with a UV fluence ( F, in J/m 2 ) is assumed described by S ( kF ) = exp( -kF ), where k is the UV inactivation rate constant (m 2 /J). The average survival fraction ( S p ) of the simulated virions in a group of particles is calculated using the energy absorbed by each virion in the particles. The results show that virions within particles of dried respiratory fluids can have larger S p than do individual virions. For individual virions, and virions within 1-, 5-, and 9-µm particles illuminated (normal incidence) on a surface with 260-nm UV light, the S p = 0.00005, 0.0155, 0.22, and 0.28, respectively, when kF =  10. The S p decrease to <10 −7, <10 −7, 0.077, and 0.15, respectively, for kF  = 100. Results also show that illuminating particles with UV beams from widely separated directions can strongly reduce the S p . These results suggest that the size distributions and optical properties of the dried particles of virion-containing respiratory fluids are likely important to effectively designing and using UV germicidal irradiation systems for microbes in particles. The results suggest the use of reflective surfaces to increase the angles of illumination and decrease the S p . The results suggest the need for measurements of the S p of SARS-CoV-2 in particles having compositions and sizes relevant to the modes of disease transmission.